Las actitudes lingüísticas de hispanohablantes de Managua y Masaya frente a las variedades del español centroamericano - Mairena Uriarte, Rosa Amanda (2021)
The purpose of this study is to identify the linguistic attitudes of Spanish speaking people in Managua and Masaya towards the six varieties of Central American Spanish: the Spanish of Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica and Panama. From a mentalistic approach, based on the responses to the productions of the informants of each country, we analyze cognitive and affective aspects of the linguistic attitudes of the citizens of Masaya and Managua. Among the relevant results, regarding the cognitive aspect of linguistic attitudes, we observe that the respondents know their own linguistic variety and that of Costa Rica, while they do not know the Spanish variety of El Salvador. With respect to the affective component, a favorable linguistic attitude towards the Central American varieties of Spanish is expressed, with the exception of Guatemalan. However, the majority would not use these varieties of Spanish.